PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) - Regina Usman (JAF (Journal of Accounting and Finance), 2017)
Local revenue (PAD) is a local earned revenue collected by the regional regulation in accordance with the legislation. Sources of revenue are derived from local tax, local retribution, regional owned enterprises and local wealth management results, and other revenues. The more the local needs can be financed by PAD, the higher the quality of the local autonomy. This study aims to determine the influence of local tax and local retribution to local revenue of Bandung period of 2011-2015 either simultaneously or partially. The population in this study is a Realized Regional Government Budget Report of Bandung in 2011-2015. Sample selection technique used is judgment sampling and obtained 60 samples, consisting of January to December 2011-2015. The data analysis method was multiple regression analysis. The results show that there is simultaneous significant difference between local tax and local retribution to local revenue. Partially, local tax has significant positive effect on PAD, while the local retribution has no significant effect on PAD